The mediating effect of employee engagement on the relationship between perceived organisational support and organisational commitment: evidence from offshore oil and gas industry / Ridwan Mokhtar - Mokhtar, Ridwan (2020)
With the rapid growth of business and changes in the economic landscape, organisational commitment has consistently been a challenging issue to be discussed in any organisations which previous literature link it closely to turnover and absenteeism issue, but those issues are lesser when it comes to oil and gas industry. Therefore, this study examines the effects of perceived organisational support towards organisational commitment among offshore employee in Malaysia oil and gas industry. This study investigates the effect of employee engagement in mediating the relationship between perceived supports and organisational commitment. This study also investigates the effect of a region in moderating the relationship between employee engagement and organisational commitment. This study had applied the social exchange theory to explain the phenomena and predict the relationships. The study had employed a quantitative study method, and the survey instrument was used in the data collection from the established sample size through G- Power software. It had applied a non-probability sampling technique using the convenience sampling method. A number of 246 completed responses we subsequently collected and the data were analysed using the PLS-SEM 3.3.0 to reach the desired findings, as outlined in the research objectives. The findings of this study suggest that the perceived organisational support has a significant relationship with organisational commitment and employee engagement does mediate the relationship between perceived organisational supports and organisational commitment, whereas region does moderate the effect of the relationship between employee engagement and organisational commitment.